2014
DOI: 10.1002/mrm.25120
|View full text |Cite
|
Sign up to set email alerts
|

Combining perfluorocarbon and superparamagnetic iron‐oxide cell labeling for improved and expanded applications of cellular MRI

Abstract: Purpose The ability to detect the migration of cells in living organisms is fundamental in understanding biological processes and important for the development of novel cell-based therapies to treat disease. MRI can be used to detect the migration of cells labeled with superparamagnetic iron-oxide (SPIO) or perfluorocarbon (PFC) agents. In this study, we explored combining these two cell-labeling approaches to overcome current limitations and enable new applications for cellular MRI. Methods We characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…More 19 F signal quenching was observed when both agents were administered simultaneously (colabeled). Quenching was also observed for colocalized cells in gradient‐echo fast low angle shot images, but not in spin‐echo rapid acquisition with relaxation enhancement images . These important observations set the stage for the work that we present here in a mouse model of stem cell transplantation and rejection.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…More 19 F signal quenching was observed when both agents were administered simultaneously (colabeled). Quenching was also observed for colocalized cells in gradient‐echo fast low angle shot images, but not in spin‐echo rapid acquisition with relaxation enhancement images . These important observations set the stage for the work that we present here in a mouse model of stem cell transplantation and rejection.…”
Section: Discussionmentioning
confidence: 81%
“…Quenching of the 19 F signal was first reported in a study by Hitchens et al that explored the quenching of signal when 19 F-labeled cells are colabeled with iron nanoparticles (45). The authors showed that the 19 F T2 was significantly reduced in cells that were labeled with both iron and 19 F, but that iron-labeled cells mixed equally with 19 F-labeled cells did not impact the 19…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The TATP-F68-PFC nanoemulsion droplets are present intracellularly and appear as clusters of small (~100-200 nm) punctate regions of hyperintensity in micrographs ( Figure 4E,F), along with a few larger PFC deposits (~1 μm) ( Figure 4G,H), presumably coalesced droplets, consistent with previous studies. 29,36 Untreated control cells did not contain these hyperintense features in micrographs ( Figure 4C,D). Similar findings were observed for CAR T cells labeled with TATA-F68-PFC nanoemulsion ( Figure 4I-L).…”
Section: Confocal Microscopy Of Car T Cells Incubated With Fluorescenmentioning
confidence: 94%
“…Molday ION is primarily used as an MRI contrast agent (see, for example, Refs. [41][42][43]. All of our permeability measurements were made using 2 mL of the Molday ION suspension.…”
mentioning
confidence: 99%